2011
DOI: 10.1152/ajpgi.00527.2010
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin stimulates expression of plasminogen activator inhibitor-1 in gastric epithelial cells

Abstract: Plasminogen activator inhibitor (PAI)-1 is associated with cancer progression, fibrosis and thrombosis. It is expressed in the stomach but the mechanisms controlling its expression there, and its biological role, are uncertain. We sought to define the role of gastrin in regulating PAI-1 expression and to determine the relevance for gastrin-stimulated cell migration and invasion. In gastric biopsies from subjects with elevated plasma gastrin, the abundances of PAI-1, urokinase plasminogen activator (uPA), and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 38 publications
3
26
0
Order By: Relevance
“…Others and we have previously reported increased migration and cell survival in response to gastrin [18, 24, 31]. In the present study, we assessed the influence of gastrin induced autophagy on both cell migration and cell survival.…”
Section: Resultsmentioning
confidence: 86%
“…Others and we have previously reported increased migration and cell survival in response to gastrin [18, 24, 31]. In the present study, we assessed the influence of gastrin induced autophagy on both cell migration and cell survival.…”
Section: Resultsmentioning
confidence: 86%
“…Twelve weeks was the maximum time permitted by the current toxicology studies in rat and dog [41]. We assessed efficacy by: counting the number of tumours; measuring the diameter of the largest tumour; measuring abundances of the gastrin-dependent genes, chromogranin A, histidine decarboxylase, matrix metalloproteinase-7, and plasminogen activator inhibitor-1 and -2 in tumour biopsies, all of which are increased in type 1 gastric NETs [42-45]; and measuring plasma CgA concentration. We assessed a range of potential tumour biomarkers, because there is no published evidence about the effect of a gastrin/CCK-2 receptor antagonist on gene expression in humans, and we wanted to prepare for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…21) and a recent in vitro study showed that gastrin plays a key role in maintaining gastric stem cells. 22 Some of these effects arise as a result of the altered expression of proteins that regulate tissue remodelling including members of the matrix metalloproteinase, 23 tissue inhibitor of metalloproteinase 24 and urokinase plasminogen activator 25 families.…”
Section: Gastric Hormonesmentioning
confidence: 99%